Om mulighederne for at reducere de offentlige udgifter til lægemidler gennem øget konkurrence - Niels Blomgren-Hansen (Copenhagen Business School (CBS), Department of Economics, 1999)
– On the possibility of reducing public expenditures on medicine through deregulation. The market for medicine is special in three essential respects: (a) The role of the buyer is divided by three agents: the (informed) doctor, who prescribes the medicine, the public health insurance, which pays most of the bill, and the (uninformed) consumer, who benefits from the medication and pays part of the bill. This division creates obvious incentive problems. (b) The distributors (pharmacies and wholesalers) have no market power as they are obliged to procure the medicine prescribed by the doctors - no more no less. (c) Competition among suppliers is limited; most medicine is provided by either a single producer of patented drugs or by a few competitors. Economic efficiency calls for some combination of regulation and competition, the exact combination depending upon the market structure of the various sub-markets. - First, we discuss the possibilities of designing an appropriate combination of administrative regulation and incentives suitable for enhancing cost-efficiency of prescription. Second, we analyse the economies of deregulating the pharmacy sector which, by now, is subject to both controls on both (total) gross profits and establishment. The conclusion is that deregulation is unlikely to increase economic efficiency. Third, we take a look at the whole sale sector which, by now, is subject to binding re-sale prices determined by the producers. Economic efficiency dictates that binding resale prices are upheld. Finally, we discuss the possibilities of strengthening the demand side as a way of reducing expenditures and recommend that the organization of the demand side should reflect the market structure of the supply side: In case of monopoly, the bargaining should be entrusted to a single, powerful public body. In case of imperfect competition, tendering appears appropriate.
hdl:10398/7492
Keywords: I11; 330; Public expenditure; Medicine through deregulation